Antifungal and antibacterial activities of polyherbal toothpaste against oral pathogens, in vitro - Batool Sadeghi-Nejad; Eskandar Moghimipour; Sedigheh Yusef Naanaie; Shahrzad Nezarat (Mazandaran University of Medical Sciences, 2018)
Background and Purpose: Herbal toothpastes are more secure and efficacious and less poisonous due to containing natural chemicals as compared with the synthetic toothpastes. The present study aimed to formulate a polyherbal toothpaste using accessible medicinal plants in Iran and evaluate its efficiency in the protection of oral hygiene and prevention of dental caries. Materials and Methods: The developed toothpaste was made of the leaf extracts of Artemisia dracunculus, Satureja khuzestanica (Jamzad), and Myrtus communis (Linn), combined at four different dilutions, namely 1:4 (25%), 1:1 (50%), 3:4 (75%), and (100%), with sterile distilled water. The product was tested against five microorganisms, including Streptococcus mutans, Lactobaccilus caseie, S. sanguis, S. salivarius, and Candida albicans, using agar well diffusion method. Results: After 24 h of incubation, the maximum mean diameters of inhibition zone against L. caseie and C. albicans were obtained as 17-30 and 10-25 mm, respectively. Furthermore, the minimum mean diameter of inhibition zone against S. salivarious was estimated as 15-20 mm. Conclusion: The formulated toothpaste showed potent inhibitory activities against Gram-positive bacteria and C. albicans. Therefore, more studies are required to accurately investigate the efficacy of the formulated toothpaste.